2013
DOI: 10.7555/jbr.27.20130008
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography analysis of curved root canals after mechanical preparation with three nickel-titanium rotary instruments

Abstract: Cone beam computed tomography is a 3-dimensional high resolution imaging method. The purpose of this study was to compare the effects of 3 different NiTi rotary instruments used to prepare curved root canals on the final shape of the curved canals and total amount of root canal transportation by using cone-beam computed tomography. A total of 81 mesial root canals from 42 extracted human mandibular molars, with a curvature ranging from 15 to 45 degrees, were selected. Canals were randomly divided into 3 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Each sample was inserted into the unset acrylic resin so that its long axis was parallel to the long axis of the mold to ensure standardization of the specimens for tomographic imaging. 10 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each sample was inserted into the unset acrylic resin so that its long axis was parallel to the long axis of the mold to ensure standardization of the specimens for tomographic imaging. 10 …”
Section: Methodsmentioning
confidence: 99%
“…D2 was the measurement of the quantity of voxels from the external surface of the distal portion of the root to the distal surface of the canal after instrumentation ( Figs 1 and 2 ). 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cone beam computed tomography (CBCT) is a recent advancement with advantages of image accuracy, acquisition of images in three planes (coronal, sagittal and axial) and reduced image artifacts. [ 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the segmentation performed on CBCT images, the results showed that, when compared to the gold standard, both the "automatic CBCT" and "visual CBCT" were statistically different compared to the gold standard, revealing a limitation of the accurate determination of root canal volume using this image modality (with acquisition parameters used in this study). Despite the accuracy of CBCT in allowing a three-dimensional and detailed view of bone 3,22 , in this study, it did not allow a precise determination of root canal volume. This may be probably explained by the specific acquisition parameters and resolution of the CBCT used.…”
Section: Discussionmentioning
confidence: 80%